Code-Based Self-Verification Effects on Phi-3-Mini and Mistral-7B GSM-Symbolic Accuracy Under Adversarial Perturbations - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 11 peer-reviewed papers addressing the following research question: How does the accuracy of Phi-3-mini and Mistral-7B-v0.1 on GSM-Symbolic change when code-based self-verification is applied to adversarially perturbed instances across multiple languages. 12 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 2.5/10. This report is a machin
Machine-generated literature synthesis.